A Study on Use of the Internet by Teachers and Students of Surkhet Campus (Education) (Surkhet Journal, 2014)
This‌ study‌ aims‌ at‌ identifying‌ percentage‌ of‌ teachers‌ and‌ students‌ using‌ the‌ Internet‌ and‌ find‌ out‌ purposes and problems of its use in Surkhet Campus (Education). Questionnaires (295) were distributed to 37 randomly selected teachers and 258 students selected from all levels, shifts, sexes and subjects using stratified‌ proportionate‌ random‌ sampling‌ method.‌ Questionnaires‌ were‌ administered‌ individually‌ to‌ the‌ teachers and collectively to the students in their classrooms to ensure the excellent (100%) response rate. The result revealed that 46.12% students and 78.37% teachers use the Internet. Many students (34.49%) and teachers (70.27%) use it for getting general information followed by accessing online newspapers (48.64%), getting help in teaching learning (45.94%), sending and receiving e-mails (43.24%), research (40.54%), chatting (37.83%), social networking (32.43%), entertainment (32.43%), Skype conversation (24.32%), downloading free software (18.91%), online education (16.21%), and downloading books and journals and studying online journals (5.40%) by teachers and chatting (28.68%), accessing online newspaper (27.51%), social networking (19.76%), sending and receiving e-mails (18.60%), getting help in teaching learning (14.72%), downloading free software (9.30%), Skype conversation, (8.13%), research (0.38%), and online studies (0.38%) by students. Many students (44.18%) and teachers (32.43%) do not use it at the campus because they do not own a device and few other problems. A good number of teachers were found habitual with varied Internet applications and services.